1996
DOI: 10.1016/0014-5793(96)01002-2
|View full text |Cite
|
Sign up to set email alerts
|

Epitope topology of Na,K‐ATPase α subunit analyzed in basolateral cell membranes of rat kidney tubules

Abstract: were processed for immunocytochemistry. Immunogold labeling using antibodies against the N-termlnus (Glyl-Hisl3), Leu siSGin s28 and the C-terminus (Ilel°°2-Tyr t°°6) was superimposed on 2. Materials and methods the images of the electron microscope protoplasmic fracture face of the basolateral plasma membranes, thus demonstrating Tissue preparation and quick:[reezingThe inner stripe of the outer medulla of rat kidneys was cut into cytoplasmic locations of these epitopes. On the contrary, SDSsections less than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
1999
1999

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In his experiments, SDS digestion was used to dissolve unfractured cell components before the immunocytochemical reactions that permitted the labeling of antigens in freeze-fractured intracellular membranes. The SDS-digested freeze-fracture replica labeling technique (SDS-FRL) has been applied to studies of epitope topology of intramembranous protein molecules (Fujimoto et al 1996a) and transmembrane topology of membrane phospholipids (Fujimoto et al 1996b).…”
Section: Discussionmentioning
confidence: 99%
“…In his experiments, SDS digestion was used to dissolve unfractured cell components before the immunocytochemical reactions that permitted the labeling of antigens in freeze-fractured intracellular membranes. The SDS-digested freeze-fracture replica labeling technique (SDS-FRL) has been applied to studies of epitope topology of intramembranous protein molecules (Fujimoto et al 1996a) and transmembrane topology of membrane phospholipids (Fujimoto et al 1996b).…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that integral membrane proteins revealed as intramembrane particles by freeze-fracture replication, which are indistinguishable on a purely morphological basis, can be selectively labeled by SDS-FRL with specific antibody (Fujimoto 1995;Furuse et al 1996). In addition, this approach can be applied to examine the transmembrane phospholipid distribution in various cell and intracellular membranes (Fujimoto et al 1996b) and the precise topological analysis of integral membrane proteins using site-directed antibodies (Fujimoto et al 1996a). In SDS-FRL, unfixed, quick-frozen cells, after freeze-fracture and platinum/carbon (Pt/C) shadowing, are treated with 2.5% SDS.…”
Section: Introductionmentioning
confidence: 99%